The causal association between iron status and the risk of autism: A Mendelian randomization study - Chen, Li; Guo, Xingzhi; Hou, Chen; Tang, Peng; Zhang, Xin; Chong, Li; Li, Rui (Frontiers in Nutrition, 2022)
Emerging evidence indicates a connection between serum iron levels and autism, but the underlying causal association is yet unclear. Thus, we performed two-sample Mendelian randomization (MR) analysis to evaluate the causal link between iron status on autism, using genetic instruments (p < 5E–08) strongly associated with iron status (N = 48,972), including serum iron, ferritin, transferrin levels, and transferrin saturation. Summary statistics of autism was obtained from two independent studies conducted by Psychiatric Genomics Consortium (PGC, Ncases = 5,305, Ncontrols = 5,305) and FinnGen Consortium (FC, Round six, Ncases = 344, Ncontrols = 258,095), respectively. Using the inverse-variance weighted (IVW) method, the combined results of PGC and FC demonstrated that genetically determined serum transferrin level was significantly associated with an increased risk of autism [odds ratio (OR) = 1.16, 95% CI: 1.03–1.30, p = 0.013]. There was no significant causal effect of serum iron (OR = 0.99, 95% CI: 0.72–1.37, p = 0.951), ferritin (OR = 0.88, 95% CI: 0.47–1.64, p = 0.676), and transferrin saturation (OR = 0.89, 95% CI: 0.72–1.09, p = 0.252) on autism. No obvious pleiotropy was found in this MR study. Taken together, our findings highlight that elevation of serum transferrin level might be associated with a high risk of autism, suggesting a potential role of iron deficiency in autism development. Future studies are warranted to clarify the underlying mechanism, which will pave a new path for the prevention and treatment of autism.